Decoding Market Valuation: Panel Regression Insights into Nepalese Commercial Banks (Pravaha, 2025)
This paper investigates the key influences, namely the Dividend payout ratio (DPR), Price-to-Earnings Ratio (P/E ratio), Earnings Per Share (EPS), Interest Rate (IR), Book Value per Share (BVPS), Return on Assets (ROA) and Stock Return (SR) on commercial banks’ Market Price per Share (MPPS). It consists the panel dataset of 10 of the 19 commercial banks listed in NEPSE. It uses the 10-years data covering from fiscal year 2013/14 to 2023/24. The fixed effect Hausman test suggests that DPR, P/E ratio, EPS, BVPS and ROA have significant impact on MPS, and P/E ratio is found to have the most influential to explain the equity price of Nepalese banks. Whereas IR and SR exert no notable effect on the prices. The results simply indicate that the market price is highly shaped by profit measure variables such as earnings, dividends, and efficiency. Future research extends incorporating a broader dataset at the population level, by employing alternative methodological approaches, macroeconomic variables, and investor behavioural issues that could provide in-depth facts in price creation process in the emerging capital markets.